2022
DOI: 10.3389/fgene.2021.801240
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Three-Gene Prognostic Signature Based on Tumor Microenvironment for Gastric Cancer

Abstract: Gastric cancer (GC), which has high morbidity and low survival rate, is one of the most common malignant tumors in the world. The increasing evidences show that the tumor microenvironment (TME) is related to the occurrence and progression of tumors and the prognosis of patients. In this study, we aimed to develop a TME-based prognostic signature for GC. We first identified the differentially expressed genes (DEGs) related to the TME using the Wilcoxon rank-sum test in a training set of GC. Univariate Cox regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The GSE 45670 dataset was utilized to evaluate immunity infiltration via the CIBERSORT algorithm. Growing evidence pointed to the underlying mechanisms by which the local immune microenvironment and immune cells drive tumorigenesis in many cancers ( Greten and Grivennikov, 2019 ; Wang Q. et al, 2021 ; Kumar et al, 2022 ). Previous studies have shown that DNA damage repair-related genes, apoptosis-related genes, cellular hypoxia-related genes, cell cycle-related genes, and autophagy genes play important roles in radiosensitivity by changing the microenvironment ( Chen et al, 2017 ; Tang et al, 2018 ; Zhang H. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The GSE 45670 dataset was utilized to evaluate immunity infiltration via the CIBERSORT algorithm. Growing evidence pointed to the underlying mechanisms by which the local immune microenvironment and immune cells drive tumorigenesis in many cancers ( Greten and Grivennikov, 2019 ; Wang Q. et al, 2021 ; Kumar et al, 2022 ). Previous studies have shown that DNA damage repair-related genes, apoptosis-related genes, cellular hypoxia-related genes, cell cycle-related genes, and autophagy genes play important roles in radiosensitivity by changing the microenvironment ( Chen et al, 2017 ; Tang et al, 2018 ; Zhang H. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Univariate Cox regression analysis was applied to assess the prognostic value of LNR-related genes, and genes with P <0:01 were identified as prognostic genes and were incorporated into least absolute shrinkage and selection operator (LASSO) regression. LASSO regression is an algorithm usually used for fitting selecting variables in high-dimensional generalized linear models [16]. We then constructed a risk score model on the basis of the expression levels and the risk coefficients (β) of prognostic genes identified by LASSO regression.…”
Section: Construction and External Validation Of The Prognosticmentioning
confidence: 99%
“…The mechanism by which PLPPR4 affects tumorigenesis appears to involve cell adhesion. Recently, PLPPR4 was identified as a tumor microenvironment-based prognostic marker for gastric cancer ( Wang et al, 2022 ). Overall, these data indicate aberrant expression of some PLPPRs in cancer lines and tissue suggesting a link to tumorigenesis.…”
Section: Expression and Localization Of Phospholipid Phosphatase- Rel...mentioning
confidence: 99%